Potensi Ekstrak Buah Delima Merah (Punica granatum Linn) terhadap Penurunan Jumlah Koloni Streptococcus mutans - Kholisa Kholisa; Purwanto Purwanto; Sri Hernawati (Pustaka Kesehatan, 2018)
Streptococcus mutans is a bacteria that initiates the formation of plaque on the tooth surface. S. mutans works by fermenting carbohydrates to produce an acidic atmosphere, so the plaque pH becomes low, this condition can lead to demineralization of enamel and dentin commonly called caries. One of alternative treatment to reduce the population of S. mutans by using herbal plants, namely red pomegranate. Red pomegranate contains flavonoids, tannins, and alkaloids as antibacterial. This study aimed to determine the inhibition of red pomegranate extract on growth of S. mutans. The method used is by counting the number of S. mutans using a colony counter. This method with 4 samples in each study group. The study group consists of 4 treatment groups (25%, 50%, 75% and 100% red pomegranate extract), positive control group (chlorhexidine), and negative control group (sterile aquades). Data were analyzed using Kruskal-Wallis Test and Mann-Whitney test. Red pomegranate extract has the ability to inhibit the growth of S. mutans. The concentration of red pomegranate extract that has the greatest inhibitory effect on S. mutans growth is 100%. Keyword: Antibacterial, Streptococcus mutans, caries, red pomegranate fruit extract